Effects of Monoolein on Ki67 Protein and Apoptosis-Related Biomarkers Expression in Cervical Cancer Implanted Nude Mice - Rongpan, Sudarat; Trongwongsa, Therdkiat; Wongsatayanon, Benjamas; Jariyapongskul, Amporn (Princess of Naradhiwas University Journal, 2022)
This study aimed to investigate the effect of monoolein (MO), a glycolipid surfactant purified from Exophiala dermatitidis on expression of cell proliferation; Ki67 and apoptosis biomarkers; TUNEL and Caspase-3 in cervical cancer xenograft in nude mouse model. HeLa cells were subcutaneously injected on the right dorsal of BALB/C nude mice to establish xenografted tumors. Mice were randomly divided into 2 groups, HeLa implanted mice (HeLa group) and HeLa implanted mice treated with MO (HeLa-MO group). Monoolein 200 mg/Kg/BW was injected subcutaneously around the tumor mass for 28 days. Tumor tissue mass of each mouse was collected for immunohistochemical examination of Ki67 and for examination of apoptosis by using TUNEL and Caspase-3 assays. The result showed that MO treatment in HeLa-MO group significantly reduced the Ki67 expression by 57.53% as compared to HeLa group (66.67±6.78 and 157±10.54, cell/field, respectively). Furthermore, TUNEL and Caspase-3 staining were remarkably increased in HeLa-MO group (118.5±6.53 and 32.76±4.51 cell/field) and (130.7±11.42 and 34.2±2.49 cell/field) as compared to HeLa group, respectively (p<0.001). In conclusion, our finding demonstrated that treatment with monoolein in cervical cancer mouse model can reduced tumor growth via inhibition of tumor cell proliferation and apoptosis pathway.